(untitled) (International Journal of Engineering and Computer Science, 2017)
Technology is making many things easier. We can say that this concept is standing example for that. So far we have seen LAN, MAN, WAN, INTERNET & many more but here is new concept of “ RED TACTON ” which makes the human body as a communication network by name HAN (Human Area Network). Red Tacton is a new Human Area networking technology that uses the surface of the human body as a safe, high speed network transmission path. Red Tacton uses the minute electric field generated by human body as medium for transmitting the data. The chips which will be embedded in various devices contain transmitter and receiver built to send and accept data in digital format. In this paper we will discuss about red tacton, and its working states, and applications of red tacton various fields. And we will compare our red tacton with the other technology for data transmission and know about human area network.